Missio Dei: Theological pressupositions of the Lutheran understanding of Mission from an analysis of Martin Luther’s “Catechism Systematic” - Schwambach, Claus (Vox Scripturae - Revista Teológica Internacional, 2025)
From Luther’s reseachers established finding that interpretation of Luther’s second petition of the Lord’s Prayer, especially in the Greater Catechism, may serve as an important reference for understanding what Luther understands by what we today call Lutheran perspective of Mission, the present study seeks to deepen the discussions on Lutheran missiology. Whereas Luther’s interpretation of the 2nd Petition of the Lord’s Prayer in the Greater Catechism needs to be understood within the whole of the Greater Catechism and the so-called “systematic of the catechism”, which reveals the larger theological background in which the 2nd Petition is embedded, the focus of the analysis will be on analyzing the theological and central elements of the “systematic of the catechism” that serve as a presupposition, framework and theological criterion for understanding the theology of mission expressed in the 2nd petition interpretation. The approach shows that, from a missiological point of view, Luther’s “systematic of the catechism” can be summarized through the expression missio Dei, and the typically Lutheran concept of missio Dei, as it is embedded in the hermeneutic assumptions of this “systematic of the catechism” Luther’s, must necessarily be distinguished from other contemporary conceptions of missio Dei, despite the undeniable closeness between these conceptions. The study also seeks to point to proximity and distances between the Lutheran tradition and other contemporary missiological conceptions, such as those of integral mission theology and missional theology.
Keywords: Mission in Martin Luther; Lutheran Missiology; Missio Dei; Mission Theology; Evangelization